Strategi Guru PAI dalam Meningkatkan Profesionalisme dan Motivasi Belajar Siswa di Madrasah Ibtidaiyah - Munawir Munawir; Arini Hikmatal; Zelda Tsania Safitri (Jurnal Keislaman)
The aim of this research is to see how Islamic Religious Education (PAI) teachers use various approaches to increase students' professionalism and desire to study at Madrasah Ibtidaiyah. PAI teachers have an important role in shaping students' character through implementing innovative learning approaches based on Islamic values. This research collects data from various relevant literature sources; Data analysis methods are used to study various learning approaches in Islamic education. The research results show that PAI teachers use various learning approaches, including role playing, question and answer, lectures, and project and problembased learning approaches.  This method has proven effective in increasing teacher professionalism and fostering students' desire to learn. In addition, methods that suit students' needs, a fun learning environment, and rewards can strengthen students' desire to learn. This research helps improve the quality of learning at Madrasah Ibtidaiyah and helps PAI teachers create better and more meaningful learning strategies.